Implementation of Certain Time Work Agreement (PKWT) in supporting company development - Adityaningrum, Narita (Universitas Syiah Kuala, 2023)
Workers/laborers are an important component for the survival of the company. The existence of contract workers with a Specific Time Work Agreement (PKWT) shows an increase, because apart from being more flexible, they are also considered more efficient. However, on the other hand, PKWT is considered not to provide a guarantee of continued income for workers after the end of the work agreement. The problem formulation is; What is the relationship between employment and the contract work system in Indonesian labor law? also what is the responsibility of the Employer or employer regarding the presence of workers with a contract system in the company? The research method uses a type of normative legal research. The approach method used is a statutory approach and a conceptual approach. Study results: the work element in the employment relationship is absolute because it is the object of the agreement. Existing work must be carried out by the worker himself based on the employer's orders. The nature of the work that is the object of the employment agreement is inherent in the employee, so that based on law, the employment agreement is terminated by law if the employee dies. The different interests between employers and workers regarding the existence of contract workers in PKWT contracts have encouraged the enactment of heteronomous employment legal norms through the Law on Employment and the Job Creation Law. Conclusion: the employment relations of contract workers based on PKWT have been regulated by terms and conditions in Law Number 13 of 2003 concerning Employment and the Employment Cluster Job Creation Law. Heteronomous employment legal norms which determine the terms and conditions of PKWT are a form of government intervention in employment relations which aims to provide justice for the existence of contract workers in companies.